Analiz vystuplenija sbornoj komandy Rossii na cempionate mira po paralimpijskoj legkoj atletike 2019 - Manuilov, S. I.; Voroshin, I. N. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
In November 2019 in Dubai (UAE) there was the Para Athletics World Championship 2019. Analysis of the results of these competitions is of great importance before the Paralympic Games 2020, which will be in three hundred days after World Championship - the first half of September 2020. In this material we made the analysis of national team performance at this competition. The Russian national team won 41 medals at this competition, including 10 gold medals. The result of the performance was the 6th team place. The competition was distinguished by high results, as evidenced by the setting up of 58 world records.